Interrupted life : experiences of incarcerated women in the United States - Solinger, Rickie, 1947- (University of California Press, 2010)
"Interrupted Life is a gripping collection of writings by and about imprisoned women in the United States, a country that jails a larger percentage of its population than any other nation in the world. This eye-opening work brings together scores of voices from both inside and outside the prison system including incarcerated and previously incarcerated women, their advocates and allies, abolitionists, academics, and other analysts. In vivid, often highly personal essays, poems, stories, reports, and manifestos, they offer an unprecedented view of the realities of women's experiences behind bars, and, taken together, they underscore the failures of imagination and policy that have too often underwritten our current prison system."--Provided by publisher.